The path to approval of new drugs for diabetes. (March 2013) - Rendell, Marc
<x xml:space="preserve">Abstract</x> Introduction: The evaluation of agents to treat elevated blood glucose is straightforward and is accomplished with short duration studies, but it is more difficult to demonstrate safety of these agents over long periods of clinical use. Numerous large studies have raised questions as to the cardiovascular risks of certain drugs such as the thiazolidinediones and even challenged the wisdom of aggressive attempts to normalize plasma glucose. As a result of this uncertainty, the FDA issued new Guidance to Industry to assess cardiovascular risk. This new approach has markedly increased the burden to achieve approval of new diabetes drugs. Areas covered: The author has reviewed the recent history of drug approvals for diabetes drugs, using MEDLINE searches and freedom of information requests to the FDA. The thiazolidinedione saga illustrates that certain risks do not clearly manifest in the relatively short duration studies needed to evaluate control of blood sugar levels. Furthermore, the UKPDS and DCCT-EDIC studies show us that the lowering of plasma glucose has a beneficial effect which can only be reliably assessed over a very long time period. Expert opinion: The present day approval process is flawed in the conception that regulatory agencies can guarantee absolute safety. It is important to acknowledge that the risk–benefit relationship for new agents can only be determined by ongoing long-term clinical experience and prolonged longitudinal controlled studies. The increased costs of thorough safety evaluations must be defrayed by early initial approval and marketing of new therapeutic agents. Patent lifetimes and marketing exclusivity should be prolonged until results of long-term studies are finalized.